(untitled) (Journal of Applied Learning and Teaching, 2023)
Despite the outstanding benefits of education to the individual and society, some students in Nigeria are saying education/schooling is a scam. No study has been undertaken to determine why students say education/school is a scam. This study aims to provide empirical evidence on the meaning of the slogan ‘education/school is a scam’, why the students are using the slogan and the way out. A semi-structured questionnaire was used to elicit information from students in public schools/institutions in two states in Nigeria. The findings show that the slogan means that uneducated people are doing better financially, and many graduates are unemployed. They also show that the students are unsatisfied with the Nigerian educational system. Poor societal values, unemployment, and poor curriculum were reasons the students gave for using the slogan. They suggested that government should provide work for graduates and that the curriculum should be more practically oriented toward skills acquisition. The implications of this study’s findings include an update of existing theories on the factors that influence students’ attitudes and beliefs about education and the need to tailor education policy, teaching methods and curriculum to meet the needs of students. This study provides empirical evidence for the slogan ‘education/school is a scam’. Further studies are needed to confirm this empirical evidence in other states in Nigeria using in-depth interviews.